Exploring Critical Success Factors for Blockchain-based Intelligent Transportation Systems - Murat Tahir Çaldağ; Ebru Gökalp (Emerging Science Journal, 2020)
Utilization of Intelligent Transportation Systems (ITS) provides increasing demands on decreasing traffic congestions, transportation safety, and environmental problems as well as increasing transportation capacity. Over the past few years, one of the most disruptive and transformational technologies, blockchain technology, has emerged. As a result of offering more security, privacy, traceability, transparency, and decentralized authority, the utilization of blockchain technology in ITS have increased drastically. Despite this increase, there is a lack of a good understanding of what are the Critical Success Factors (CSF) to support IT providers for designing their products properly, and to provide industry leaders to focus on the main drivers of their outstanding projects. This study aims to explore and analyze CSFs that can facilitate the success of blockchain-based ITS, which has so far been neglected despite its remarkable relevance. In doing so, eleven primary studies, identified as a result of conducting a systematic literature review (SLR), were taken as a baseline to develop the model of CSFs. Additionally, since the number of existing studies related to CSFs for blockchain and ITS are limited, an expert panel was formed to evaluate and contribute to the model. The developed model of CSF for blockchain-based ITS, having a comprehensive approach, consists of 29 CSFs defined under five main contexts, namely technical, management, governance, quality of service, and quality of life. Doi: 10.28991/esj-2020-SP1-03 Full Text: PDF